Determination of mercury methylation potential in the presence of peat organic matter - Vinicius, Marques Gomes [UNESP] (2013)
Methylmercury (MeHg) is a neurotoxin pollutant that accumulates in organisms and biomagnifies along the trophic chain. It is formed by the transfer of a methyl group to inorganic mercury (Hg). This transformation, termed methylation, can occur as a result of microbial activity, photochemical transfer of the methyl group, or interaction with humic substances present in water bodies, with microbial activity showing the greatest methylation potential. In this work, the formation of MeHg was observed over a period of 22 days, in the presence of peat rich in organic matter (OM), together with either Hg0 or Hg2+. Analyses were made of pH, redox potential (EH), and dissolved oxygen (DO).